PEMELIHARAAN BENIH IKAN BAUNG (Hemibagrus Nemurus) DENGAN TEKNOLOGI PHOTOPERIOD - Benny Heltonika; Okta Rizal Karsih (Fakultas Perikanan dan Kelautan, Universitas Riau, 2017)
The problem of Hemibagrus nemurus culture is availability of fish fingerlings, because H. nemurus have cannibal character on fingerlings phase. From several research shown result that photoperiod can decrease cannibal character in some catfish. Based on that information this research has been done. Aimed of this research was to known effect of photoperiod to H. Nemurus fingerlings om growth and survival rate. This research used 3 treatment and 3 repetition, the treatment was cultivation of H nemurus fingerling on 24 hours on day (treatment 1), 12 on dark and 12 on day (treatment 2) and on 24 hours on dark (treatment 3). Result of this research was fingerlings of H. nemurus were rared on 24 hours dark gived significant growth and survival rate. Form survival rate can showed that cannibal character at h. nemurus fingerlings where rared on 24 darks has been decrease.